2003
DOI: 10.1016/j.hep.2003.09.031
|View full text |Cite
|
Sign up to set email alerts
|

Separate Analysis of Asialoglycoprotein Receptors in the Right and Left Hepatic Lobes Using 99MTc–Gsa Spect

Abstract: The asialoglycoprotein receptor (ASGPR) is abundantly expressed on the sinusoidal surfaces of hepatocytes. We aimed to clarify the clinical significance of the regional distribution of ASGPRs in the human liver, especially in chronic viral hepatitis. Eighteen volunteers, 34 patients with chronic hepatitis, and 33 patients with cirrhosis (11/Child-Pugh A, 11/Child-Pugh B, 11/Child-Pugh C) were studied using a newly developed, conventional technetium-99m-diethylenetriaminepentaacetic acid-galactosyl human serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 26 publications
0
33
0
Order By: Relevance
“…To (55). Liver functional volume (by outline extraction method), liver uptake ratio, and liver uptake density were calculated in patients with different severities of parenchymal liver disease.…”
Section: Kinetics and Quantitative Measurement Of Liver Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…To (55). Liver functional volume (by outline extraction method), liver uptake ratio, and liver uptake density were calculated in patients with different severities of parenchymal liver disease.…”
Section: Kinetics and Quantitative Measurement Of Liver Functionmentioning
confidence: 99%
“…Several studies evaluated increased FRL function after PVE using 99m Tc-GSA scintigraphy (46,(53)(54)(55)(56)(57). In 2 studies, the increase in FRL function after PVE was measured by dynamic 99m Tc-GSA SPECT and was compared with an increase in FRL volume, measured by CT volumetry, in cirrhotic and noncirrhotic patients (53,57).…”
Section: Kinetics and Quantitative Measurement Of Liver Functionmentioning
confidence: 99%
“…Although we used LHL15 and the total count ratio to represent the liver reserve capacity, radioactivity counts exist outside the SPECT scanning levels. Sugahara et al reported that the index of liver counts/syringe counts for Tc-99m GSA immediately before intravenous injection was 55.9±10.2% in Child A patients and 38.1±12.4% in Child B patients, demonstrating the clear differentiation of liver reserve capacities [14] . Therefore, LHL15 and the total count ratio might be incorporated into this index.…”
Section: Discussionmentioning
confidence: 98%
“…The SPECT data (90 steps, 360°) were obtained at 20 min with an image matrix of 128×128 and zoom of 1.28. Image reconstruction was conducted with the ordered subset expectation maximization (OSEM) method and Chang's attenuation correction [14] .…”
Section: Spect Analysismentioning
confidence: 99%
“…Recently, novel tests of FLR, such as serum HA level (13 -15), GSA scintigraphy (16), and interleukin levels (17), have been used to evaluate post-surgical complications. Furthermore, the correlation of LHL15 and HH15 to ICGR15 using a linear regression model and the analysis of individual liver segments by dynamic SPECT are easy and convenient methods for predicting hepatic functional reserve by GSA scintigraphy (18)(19)(20)(21). Therefore, our perioperative protocol for HC patients includes : the drugs (e.g.…”
Section: Introductionmentioning
confidence: 99%